2006
DOI: 10.1111/j.1538-7836.2006.02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of prostaglandin-endoperoxide synthase 2 gene, and prostaglandin-E receptor 2 gene, C-reactive protein concentrations and risk of atherothrombosis: a nested case–control approach

Abstract: Summary. Objective: Recent data have shown an association between polymorphisms of prostaglandin-endoperoxide synthase-2 gene (PTGS2; alias COX-2), and prostaglandin-E receptor-2 gene (PTGER2) and risk of atherothrombotic disorders. Methods: We evaluated two PTGS2 (rs20417, rs689470), and three PTGER2 (rs708494/uS5, rs708495/uS7, and chr14: 50 764 013/uS10) gene polymorphisms among 600 Caucasian male participants of the PhysiciansÕ Health Study with incident myocardial infarction (MI) or ischemic stroke and 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 23 publications
0
30
2
3
Order By: Relevance
“…But contrary to those results, Hegener et al (2006) found no evidence of an association of the Cox-2 polymorphisms with risk of MI. Furthermore, Kohsaka et al (2008) recently reported that the Cox-2 (-765G > C) polymorphism was, in fact, a risk factor for incident stroke in African-Americans and the result was the same for diabetic stroke cases.…”
Section: Discussioncontrasting
confidence: 54%
“…But contrary to those results, Hegener et al (2006) found no evidence of an association of the Cox-2 polymorphisms with risk of MI. Furthermore, Kohsaka et al (2008) recently reported that the Cox-2 (-765G > C) polymorphism was, in fact, a risk factor for incident stroke in African-Americans and the result was the same for diabetic stroke cases.…”
Section: Discussioncontrasting
confidence: 54%
“…The C allele may also be associated with lower levels of inflammatory markers such as C-reactive protein and interleukin-6 in cardio/cerebrovascular and hypercholesterolemic patients (Sowers et al, 2005). In contrast to these prior data, Hegener et al (2006) found no evidence for an association of the polymorphism with risk of incident CAD (Delgado et al, 2004). Furthermore, Kohsaka et al (2008) have recently reported that the -765C allele is in fact a risk factor for incident stroke in African-Americans (Bresalier et al, 2005).…”
Section: Discussioncontrasting
confidence: 51%
“…COX-2 has been found to be upregulated in atherosclerotic plaques (Kuge et al, 2007), and the polymorphisms of its gene, designated as PTGS2, have previously been associated with ischemic heart disease and risk of stroke (Colaizzo et al, 2006;Orbe et al, 2006). However, several studies indicated that there may be no association between PTGS2 polymorphism and CAD (Hegener et al, 2006;Lee et al, 2008). Therefore, we systematically reviewed the data published to date on the relationship between PTGS2 polymorphism and CAD risk and quantitatively summarized the available evidence by performing a formal meta-analysis.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…20 SNPs in genes from the fatty-acid biosynthetic and metabolic process pathways, particularly those participating in the synthesis of prostaglandins (eg, ALOX5, ALOX5AP, ALOX12, ALOX15, PTGS1, PTGS2, and COX2), have also been identified as risk factors for atherosclerotic plaque burden and CHD events. [21][22][23][24][25][26] SNPs in other genes from these pathways modulate CHD risk, presumably through their effects on lipids. [27][28][29][30][31] Thus, inclusion of these genes among enriched gene sets is supported by existing scientific literature.…”
Section: Discussionmentioning
confidence: 99%